2018
DOI: 10.3390/nu10060657
|View full text |Cite
|
Sign up to set email alerts
|

Acute Caffeinated Coffee Consumption Does not Improve Time Trial Performance in an 800-m Run: A Randomized, Double-Blind, Crossover, Placebo-Controlled Study

Abstract: Introduction: Studies evaluating caffeinated coffee (CAF) can reveal ergogenic effects; however, studies on the effects of caffeinated coffee on running are scarce and controversial. Aim: To investigate the effects of CAF consumption compared to decaffeinated coffee (DEC) consumption on time trial performances in an 800-m run in overnight-fasting runners. Methods: A randomly counterbalanced, double-blind, crossover, placebo-controlled study was conducted with 12 healthy adult males with experience in amateur e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 22 publications
4
34
1
1
Order By: Relevance
“…Graham et al (1998) reported no difference between caffeinated coffee (caffeine dose of 4.45 mg/kg) and decaffeinated coffee in an endurance running task. Marques et al (2018) found that caffeinated coffee (providing 5.5 mg/kg of caffeine) did not enhance 800m time trial run performance when compared to decaffeinated coffee. Lamina and Musa (2009) utilized caffeine doses of 5, 10 and 15 mg/kg, delivered through powdered coffee dissolved in 200 ml of water, finding no ergogenic effect of any caffeine dose on 20m shuttle run performance.…”
Section: Does Caffeinated Coffee Provide An Ergogenic Benefit?mentioning
confidence: 87%
See 2 more Smart Citations
“…Graham et al (1998) reported no difference between caffeinated coffee (caffeine dose of 4.45 mg/kg) and decaffeinated coffee in an endurance running task. Marques et al (2018) found that caffeinated coffee (providing 5.5 mg/kg of caffeine) did not enhance 800m time trial run performance when compared to decaffeinated coffee. Lamina and Musa (2009) utilized caffeine doses of 5, 10 and 15 mg/kg, delivered through powdered coffee dissolved in 200 ml of water, finding no ergogenic effect of any caffeine dose on 20m shuttle run performance.…”
Section: Does Caffeinated Coffee Provide An Ergogenic Benefit?mentioning
confidence: 87%
“…In summary, when compared to decaffeinated coffee, there is some evidence that caffeinated coffee, providing a typically ergogenic caffeine dose of 3-6 mg/kg, may enhance aerobic endurance performance (Wiles et al, 1992;Hodgson et al, 2013;Clarke et al, 2016), and can lower RPE during exercise (Demura et al, 2007). However, these findings are equivocal, with some authors reporting no ergogenic effect of caffeinated compared to decaffeinated coffee (Marques et al, 2018;Graham et al, 1998;Lamina & Musa 2009;Church et al, 2015;Anderson et al, 2018). The limited research regarding resistance and high-intensity exercise tentatively suggests no benefits to caffeinated coffee above decaffeinated coffee (Richardson & Clarke, 2016;Clarke et al, 2016), but this area merits further research.…”
Section: Insert Table 1 Around Herementioning
confidence: 99%
See 1 more Smart Citation
“…24,65,67 Bunun aksine aktif erişkin erkeklerde çözünebilir kahve tüketiminin anaerobik güç çıktısına ve 800 m koşu performansına etkisi olmadığını gösteren çalışmalar da vardır. 68,69 Farklı formlarda hazırlanmış kahvenin performansa etkilerinin araştırıldığı çalışma örneklerinde Türk usulü hazırlanan kahvenin (3 mg/kg) 5 km performansında artış sağladığı, bunun aksine ise 2 haftalık düzenli Türk kahvesi tüketiminin (474 mg kafein), 50 km bisiklet performansına etkisinin olmadığı da belirtilmiştir. 70,71 Adölesan ve çocuklarda kafein tüketimi artmasına rağmen atletik performansa etkileriyle ilgili araştırmalar nispeten daha azdır.…”
Section: Discussionunclassified
“…An additional way in which caffeine is ingested is via coffee [ 161 ]. Whilst coffee, as a method of caffeine ingestion, has been shown to be ergogenic [ 162 ], although not unequivocally [ 163 ], the question remains as to whether it is as effective as caffeine in isolation at improving performance. Graham [ 4 ] concluded that coffee was “probably inferior to caffeine as an ergogenic aid,” and that some of its multiple compounds may reduce the ergogenic effects of caffeine.…”
Section: What Else Do We Need To Know About Caffeine In Sport?mentioning
confidence: 99%